Economic Report on Africa 2024 - United Nations Economic Commission for Africa (United Nations, 2024)
The Economic Report on Africa 2024 lays out the case for investing in a just and sustainable transition to meet the aspirations of the 2030 Agenda and Agenda 2063 for building a prosperous Africa. Building on country case studies and the findings and recommendations of previous Reports touching on structural transformations and sustainability transitions, the 2024 Report assesses the conditions for pursuing that transition in Africa and for catalysing the needed investments. African countries can leverage the global boom in “green” minerals and their large renewable-energy resources, tropical forests, and marine ecosystems to export premium carbon credits, generating finance for sustainable investments. International financing through multilateral development banks and other mechanisms for climate action could leverage additional funding from other sources.